Tinjauan Hukum Dan Hak Asasi Manusia Terhadap Pelanggaran Pemanfaatan Kawasan Hutan Dalam Pembangunan Strategis Yang Memicu Banjir Bandang Di Sumatera Tahun 2025 - Kreza Surowardi Suhendar (Journal of Innovative and Creativity, 2026)
The flash flood and landslide disasters that struck Aceh, North Sumatra, and West Sumatra in late November 2025 claimed more than 900 lives and caused economic losses reaching Rp 68.67 trillion. This paper seeks to normatively examine various provisions regarding the utilization of forest areas for the realization of strategic development projects, which have become the cause of the Sumatra flash flood problem at the normative level. By applying normative legal research methods, the main findings indicate various problems in the use of forest areas for strategic development interests, including attempts to legitimize illegal forest area utilization, and the absence of legal provisions regarding remediation in cases of forest area use violations that caused the Sumatra floods, and absence of legal guarantees for non-recurrence of the violation. These conditions contradict the principles contained in the Guiding Principles on Business and Human Rights (UNGPs).